1998
DOI: 10.1177/074823379801400105
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Consumption of Lake Ontario Salmon in Rats Produces Behavioral Changes in the Offspring

Abstract: The current study assessed the effects of maternal, paternal, or combined parental consumption of Lake Ontario salmon in rats on the behavior of their offspring. Adult female Sprague-Dawley rats were put on a 30 day diet of either ground rat chow containing 30% Lake Ontario salmon (LAKE) or 30% Pacific Ocean salmon (OCEAN). These females were then mated with adult male rats similarly exposed (LAKE or OCEAN). An additional control group of males and females who were fed ground rat chow (MASH) only were also mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Animal studies of prenatal and postnatal exposures to PCBs show a relationship between PCBs and motor activity and hyperactivity (Agrawal et al, 1981; Carpenter et al, 2002; Daly et al, 1998; Holene et al, 1998; Schantz et al, 1997). Other behaviors similar to aspects of ADHD appear to be associated with PCB exposure in animals.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies of prenatal and postnatal exposures to PCBs show a relationship between PCBs and motor activity and hyperactivity (Agrawal et al, 1981; Carpenter et al, 2002; Daly et al, 1998; Holene et al, 1998; Schantz et al, 1997). Other behaviors similar to aspects of ADHD appear to be associated with PCB exposure in animals.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have shown that ingestion of fish contaminated with PCBs and other persistent organochlorines during pregnancy is associated with a lower growth rate and intellectual capacity in infants (Jacobson et al, 1990;Jacobson and Jacobson, 1997;Rogan and Gladden, 1991;Stewart et al, 2003). Laboratory studies testing POP mixtures in animals have also reported neurological deficits and systemic effects (Arnold et al, 1998;Chu et al, 1984;Daly et al, 1998;Hany et al, 1999aHany et al, , 1999bIverson et al, 1998;Seegal et al, 1998). Daly et al (1998) have demonstrated that offspring of female rats that consumed a diet containing 30% Lake Ontario salmon, known to contain POP contaminants, showed an increased reactivity to frustrative non-reward.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory studies testing POP mixtures in animals have also reported neurological deficits and systemic effects (Arnold et al, 1998;Chu et al, 1984;Daly et al, 1998;Hany et al, 1999aHany et al, , 1999bIverson et al, 1998;Seegal et al, 1998). Daly et al (1998) have demonstrated that offspring of female rats that consumed a diet containing 30% Lake Ontario salmon, known to contain POP contaminants, showed an increased reactivity to frustrative non-reward. Seegal et al (1998) have shown that rats fed a diet containing 20% Lake Ontario fish perinatally and as adults had significant reductions in brain biogenic amine functions.…”
Section: Introductionmentioning
confidence: 99%